Pelatihan Pemasaran Online Berbasis Marketplace Bagi Kelompok Ibu PKK di Desa Kalianan Krucil Probolinggo - Syafiih, M.; Khairi, Matlubul; Rasidi, Moh; Ariska, Ida; Rahayu, Sri Indra; Hati, Suci (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Internet users in Indonesia as of January 2023 reached 215.63 million or equivalent to 78.19% of the total population of Indonesia. The increase in internet users has an impact on shifting the paradigm of a new way of working. Kalianan Village is one of 14 villages in Krucil Sub-district located on the slopes of Mount Argopuro at an altitude between 1000-1300 meters above sea level with an area of 1,328.62 ha. So far, ganyong tubers in Kalianan Village are still processed as food stew to be consumed as a complement to food. Community service aims to socialize the utilization of ganyong tubers as an alternative source of nutrition and economic value that can be processed into cake raw materials. The method used in this community service activity is the Participatory Action Research (PAR) method in the form of mentoring and training in the use of marketplaces to market ganyong tuber products. Through this activity, it has an impact on increasing the average knowledge and skills from 57.5 to 95. This community service activity received a very positive response with a satisfaction level of 87.03% with a very satisfied.